“Mundo de singulares afinidades secretas” : o inconsciente nas passagens de Walter Benjamin - Mattos, Manuela Sampaio de (2019)
This thesis seeks to penetrate the ground of Walter Benjamin’s Arcades Project, with the purpose of presenting the layers of the concept of the unconscious operating in this unfinished work. Benjamin's philosophy demonstrates objectively that the rational movement can no longer assert itself in the totalitarian aspect of Reason, so his thought turns to the remaining objects of history, since they preserve the aesthetic expression of truth, so that the thuth is not outside them, in transcendental categories belonging to the cognoscent subject. With the Arcades Project, Benjamin had the goal of constructing a materialistic philosophy of history that would be able to deal with these remaining objects of history, and added to this structure of thought a character of visuality. In this sense, he wanted to present these persisting objecs through an imagerie, a concept that communicates with the idea that there is an unconscious that brings together a world of secret affinities and produces the images that constitute this imagerie. Through this writing, we attempt to demonstrate how Benjamin constructed for his theory an unique concept of the unconscious, based on the premise of the decline of experience, in the understanding that the classical conscious subject of knowledge can only be conceived since its own disaggregation, and taking under consideration the consequent necessity of dialectical integration of the unconscious thought as a knowledge not yet known in the construction of philosophical thought. In order to present this dimension of the not yet known knowledge, Benjamin introduces the concept “unconscious of the collective” quite related to the individual unconscious of Freud, and very apart from the collective and archaic unconscious of Jung. The present work begins with an introduction of the Arcades Project, passing by the new epistemological proposal suggested by Benjamin in this work, to finally conclude with the presentation of some expressions of the unconscious of the collective in the Arcades Project, sometimes resorting to other benjaminian texts to support the interpretations launched in the course of this writing composition.